Distribución horizontal y vertical del zooplancton en un ciclo diario en el litoral de una laguna pampásica - Benitez, Hernan Hugo (2009)
The vertical and horizontal distributions of zooplankton were investigated in the littoral zone of the San Miguel del Monte Lake (Buenos Aires, Argentina) in five occasions with a diel time scale (24 h) in summer. Sixty zooplankton species were recorded. The measured parameters (conductivity, temperature, dissolved oxygen, pH) showed minimal differences among the sampling occasions. Statistically significant horizontal and vertical zooplankton abundance gradients occurred. The majority of the small-bodied zooplankton (ciliates and rotifers) did not show a significant change in the horizontal or vertical distribution. Only Tintinidium fuviatile and Keratella tropica showed a significant avoidance of the surface during midnight, whereas in the same time Keratella americana showed significant aggregating in the littoral sector more distant to the edge. The spatial distribution of large-bodied zooplankton varied according diel scale. The cladocerans (Bosmina huaronensis and Diaphanosoma birgei) exhibited significant changes in horizontal position with the greatest avoidance of shore during midnight. The copepods (Notodiaptomus incompositus and Metacyclops mendocinus) showed a pronounced diel vertical differentiation, and were more abundant at surface at sunset and midnight. The high inorganic turbidity recorded (transparency: 0.35 m) could reduce the risk of predation and for this reason some zooplankters exhibit limited changes of their spatial distribution during the diel cycle.